1993
DOI: 10.1007/bf02257400
|View full text |Cite
|
Sign up to set email alerts
|

Stimulant drugs and vigilance performance: a review

Abstract: The literature on the effects of some stimulant drugs (amphetamine, methylphenidate, caffeine, and nicotine) on vigilance performance is reviewed. Improvement of overall level of performance (both accuracy and speed) after the intake of amphetamine, caffeine, and nicotine has often been reported, and the decrement in performance with time has been shown to be prevented especially with amphetamine and nicotine. Effects on false alarms are negligible. In studies where a test battery was employed, vigilance tasks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
167
1
3

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(198 citation statements)
references
References 99 publications
(68 reference statements)
27
167
1
3
Order By: Relevance
“…More importantly, in the nondeprived condition, nicotine produced modest enhancement of attentional and computational performance beyond baseline. This issue of primary enhancement vs withdrawal relief has been central to the debate on the performance effects of nicotine (Heishman et al, 1994;Hughes, 1991) and other psychomotor stimulants (James and Rogers, 2005;Koelega, 1993). In this study, we tested the same smokers after overnight tobacco deprivation and during ad libitum smoking, which allowed an unequivocal determination that nicotine normalized deprivation-induced deficits and enhanced cognitive abilities in the nondeprived condition.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, in the nondeprived condition, nicotine produced modest enhancement of attentional and computational performance beyond baseline. This issue of primary enhancement vs withdrawal relief has been central to the debate on the performance effects of nicotine (Heishman et al, 1994;Hughes, 1991) and other psychomotor stimulants (James and Rogers, 2005;Koelega, 1993). In this study, we tested the same smokers after overnight tobacco deprivation and during ad libitum smoking, which allowed an unequivocal determination that nicotine normalized deprivation-induced deficits and enhanced cognitive abilities in the nondeprived condition.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulant drugs are commonly reported to improve performance in humans (e.g., Koelega, 1993;Weiss and Laties, 1962). Studies have shown that stimulants, such as nicotine, caffeine, and amphetamines, can allay fatigue, increase vigilance, speed reaction time, prolong effort, and generally increase work output (for review, see Koelega, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that stimulants, such as nicotine, caffeine, and amphetamines, can allay fatigue, increase vigilance, speed reaction time, prolong effort, and generally increase work output (for review, see Koelega, 1993). The stimulant drugs, methylphenidate (Ritalin) and d-amphetamine, are prescribed to treat behavioral and cognitive impairments associated with attention deficit/hyperactivity disorder (ADHD) and other disorders of self-control (Tannock, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amphetamine has well-documented effects on psychomotor and cognitive function (Koelega 1993), and there is some evidence that its effects on vigilance are more pronounced than its effects on motor performance. Two previous studies have shown that low doses of amphetamine (5 to 10 mg) improve performance of an auditory vigilance task, while leaving a simple motor task (finger tapping) unaffected (Bye et al 1973;Hamilton et al 1983).…”
mentioning
confidence: 99%